Chronic hepatitis C responds poorly to combination therapy in chronic hepatitis B carriers - (:unkn) unknown (VAN ZUIDEN COMMUNICATIONS, 2008)
Background: The effect of conventional interferon-based therapy of hepatitis B virus (HBV) and hepatitis C virus (HCV) dual infection is controversial. Yet, no studies have been carried out into pegylated interferon treatment for chronic HBV/HCV coinfection. We aimed to evaluate the response rate and side effects of conventional or pegylated interferon combined with ribavirin on chronic HBV/HCV coinfection therapy. Methods: The study included 36 chronic hepatitis patients (M/F: 28/8, mean age 47 12 years) who were positive for HBsAg and anti-HCV. They were tested for the presence of HBV-DNA by hybridisation assay, and the samples giving negative results were retested by polymerase chain reaction (PCR). All patients were tested for HCV-RNA using PCR, and the HCV genotype was determined. Results: Nineteen patients were given standard interferon either alone or in combination with ribavirin, whereas 17 were given pegylated interferon and ribavirin combination therapy. None of the patients had HBV-DNA positivity; however, all had HCV-RNA detectable by PCR. All the patients had HCV genotype 1b. The mean alanine aminotransferase and aspartate aminotransferase levels were 118 +/- 65 U/l and 90 +/- 95 U/l respectively. Five patients in each group discontinued the treatment due to side effects. Only two patients (one from each group) reached sustained virological response. Conclusion: Neither pegylated nor conventional interferon based regimes were effective for HBV/HCV coinfection, in which the dominant virus was HCV. Pegylated interferon and ribavirin therapy was not superior to conventional interferon based regimes in the treatment of HBV/HCV coinfection.
Keywords: chronic hepatitis B; chronic hepatitis C; co-infection; dual infection; pegylated interferon; INTERFERON-ALPHA-2B PLUS RIBAVIRIN; CHRONIC LIVER-DISEASE; ALPHA-INTERFERON; VIRUS-INFECTION; DUAL INFECTION; COINFECTION; HCV; REPLICATION; PATIENT; HBEAG